La pietra del bando - Povolo, Claudio (Acta Histriae, 2017)
First of all, the banishment penalty refl ected the political and constitutional European polycentrism and its interrelations with a society for a long time animated by confl icts between factions and family groups. To reach a lasting peace between the opponents was indeed an essential moment of the vendetta system, as much as ensuring tranquillity and the safekeeping of the community's values. The system was endowed with a pronounced juridical dimension and it interacted, on the constitutional level, with the role played by the courts and, in particular, trial and customary rites. These were aimed to manage confl icts between opposite groups by pulling away the one who broke social stability through banishment, if necessary. During the Sixteenth century, a series of important social, demographic and economic problems sensibly reshaped the conception of social control and order, and the long-established management of penal justice as well. The banishment penalty, no longer embedded in its traditional constitutional dimension and harshened both in its repressive and rewarding aspects, became an effi cient instrument to impose a diff erent political legitimacy. Faced with these transformations, bandits quickly took the physiognomy of actual outlaws, painted as political opponents and, as such, to be dealt with any repressive instrument available.
Keywords: banditizem; izobčenci; kazen izgona; kazensko pravo; maščevanje; ponižanje; zgodovina zgodnjega novega veka